The Malaysian bat conservation research unit from a national model to an international network - Kingston, T; Juliana, S.; Nurul-Ain, E.; Hashim, R.; Zubaid, A. (Penerbit Universiti Kebangsaan Malaysia, 2012)
To have even a small chance of averting the crisis decimating Southeast Asian biodiversity, conservation researchers and practitioners need to provide policy makers with information that can guide their decisions. Particularly needed are realistic projections of the responses of diversity to different planning or policy decisions, and the attendant ecological and economic consequences of these responses. Unfortunately, there is a substantial short-fall between the information needed and our capacity to provide it, but we suggest that collaborative efforts that integrate research, capacity building and outreach can both accelerate knowledge development and transfer within the research community, and promote public understanding and appreciation of biodiversity, particularly of low-profile or unpopular taxa. The Malaysian Bat Conservation Research Unit (MBCRU) was established in 2001 to promote the conservation of Malaysia’s unique but threatened bat diversity through long-term conservation research, capacity building and outreach. Here we summarize the main activities of this integrated program, and trace the scale-up of the MBCRU model to the regional level with the launch in 2007 of the Southeast Asian Bat Conservation Research Unit (SEABCRU).